Implementasi Model Pembelajaran sentra pada Lembaga taman kanak-kanak di Kecamatan Tebo Tengah - Nur Aina; Irham. M (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to describe the implementation of center-based learning in kindergarten institutions located in Tebo Tengah District. This research employed a qualitative approach, focusing on data related to the administration of the center learning model, the stages of center learning, the implementation of center activities, and children’s developmental progress achieved through the learning process. The objects of this study consisted of two institutions in one district, namely TK Al-Azhar Tebo and TK Alhimmah Muara Tebo. The subjects included teachers, principals, and students. Data collection techniques involved passive participant observation, semi-structured interviews, and documentation. The results of this study indicate that the kindergartens in Tebo Tengah District implement center-based learning using the three play scaffolding stages: pre-play scaffolding, during-play scaffolding, and post-play scaffolding. However, each institution shows differences in the execution of center learning, time allocation, and teacher assignments.